Efeito do tipo de gás de proteção sobre o desempenho do arame tubular AWS E71T-1, utilizando processo convencional e pulsado - Sales, Juscelino Chaves (2002)
The flux cored wire AWS E71T-1 has been used in the vast majority of its applications with pure CO2 as a shielding gas. A recent study demonstrated that it is possible to improve the metallurgical characteristics of the weld metal of the flux cored wire by the application of a mixture of CO2 and argon. However, information for this gas mixture hasn’t been raised sufficiently concerning the operational performance of the wire using this gas mixture. It is known that the gas type also affects the metal transfer, the behavior of arc welding, the weld bead geometry, the deposition rate and the deposition efficiency of the wire within other characteristics of the welding process. The aim of the study consists in the realization of a survey of the AWS E71T-1 flux cored wire operational characteristics (economic characteristics of the welding consumable, geometric weld characteristics, arc stability and metal transfer). Due to this, bead on plate welding was performed using the flux cored wire AWS E71T-1 with a diameter of 1,2 mm, in flat position on samples of ABNT 1020 steel with a size of 150x50x8 mm. An electronic welding source and a positioning system were used. It was sustained a welding tension of 23 V. The relationship between the wire feed speed and the travel speed was kept constant between 20 and 23 to guarantee a deposit area of approximately 18 mm2. The influence of shielding gas (CO2 and Ar and CO2 ), the contact tube-to-work (TTW) (20 and 25 mm), the welding current (160, 180 and 200 A) and its nature (conventional and pulsed) were analyzed regarding the behavior of arc welding, the weld geometry and the economic characteristics of cored wire (fusion rate, deposition rate and deposition efficiency). The results showed that the shielding gas type has more influence on metal transfer and welding geometry and little influence on economic characteristics of the cored wire. It was also shown that the effect of the current intensity on the operationally of the flux cored wire AWS E71T-1 depends perceptibly on the current type (conventional or pulsed).